Sex‐specific differences in somatic investment and strategies of physical activity among Portuguese schoolchildren. Issue 2 (2nd June 2021) - Zorrilla‐Revilla, Guillermo; Rodrigues, Daniela; Machado‐Rodrigues, Aristides M.; Mateos, Ana; Rodríguez, Jesús; Padez, Cristina
Abstract: Objectives: Physical activity (PA) is required for healthy growth, development, and maturation and plays an important role in the prevention of overweight and obesity in childhood and adolescence. Sex‐differences in PA levels are well documented, with boys spending more time in PA, especially in moderate‐to‐vigorous activities. Following the Life History Theory, our aim is to study if PA affects the fat tissues increases during childhood and juvenile phases in both sexes. Methods: Time spent in sedentary, light, and moderate‐to‐vigorous PA levels were measured in a sample of 415 Portuguese children and juveniles (207 females/208 males; aged 6–11 years), using an accelerometer for 7 days. Skinfolds related with body fat were objectively collected and socioeconomic status factors were reported using a parental questionnaire. Results: The outcomes show that girls' and boys' fat variables increased during the end of the childhood and the juvenile phase. However, these variables were differently affected by PA. Girls increased fat variables with the sedentary activity while boys decreased fat variables with moderate‐to‐vigorous PA. Alike, active boys but not girls reduced the fat increase tendency with age. Conclusions: Although both sexes displayed a general fat increment with age, moderate‐to‐vigorous PA dampens the increase only in boys. In fact, active girls increased body fat in the same manner as non‐active girls. From an evolutionary perspective, it could explain sex‐specific somatic strategies related to future reproduction or, with future mating and intrasexual competition.